The authority of consensus and its applications in high-level transactions - Abdul Kadir, Abdul Halim; Zakaria, Mohammad Ikram; Ramlan, Muhammad Azzri Rifqi; Azlan, Muhammad Syauqi; Wan Zulkurnain, Wan Muhammad Nasrul Haq (2024)
In the study of Islamic jurisprudence, understanding the sources of reference is crucial to ensuring that practices and decisions are based on correct legal principles. In this context, there are four main sources that are considered references in the development of Islamic jurisprudence: the Holy Quran, the Sunnah, consensus, and analogy. The importance of reference sources in Islam is that these sources form the basis of Islamic legislation and provide moral guidance and guidance for Muslims. The Holy Quran is considered the main source of revelation from Allah, followed by the Sunnah, which clarifies and complements the teachings of the Quran through practical examples from the life of Prophet Muhammad, peace be upon him. Consensus, as the third source, plays an important role in determining agreement among scholars on issues not directly mentioned in the Quran or Sunnah. This shows that Islamic jurisprudence is not static, but can adapt to developments over time and social contexts. Qiyas, or analogy, also allows scholars to apply existing legal principles to new cases based on similarities in causes (Fahmi, 2013).